1999
DOI: 10.1212/wnl.52.9.1908
|View full text |Cite
|
Sign up to set email alerts
|

Falling asleep at the wheel: Motor vehicle mishaps in persons taking pramipexole and ropinirole

Abstract: The authors report a new side effect of the dopamine agonists pramipexole and ropinirole: sudden irresistible attacks of sleep. Eight PD patients taking pramipexole and one taking ropinirole fell asleep while driving, causing accidents. Five experienced no warning before falling asleep. The attacks ceased when the drugs were stopped. Neurologists who prescribe these drugs and patients who take them should be aware of this possible side effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
307
2
23

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 647 publications
(346 citation statements)
references
References 5 publications
14
307
2
23
Order By: Relevance
“…70 The dopamine agonists, bromocriptine, and pramipexole, as well as L-dopa, have been reported to cause excessive daytime sleepiness. 71,72 Patients should be informed of the potential sedative side effects of dopaminergic medication and its implication on safe driving.…”
Section: Medication Related Effectsmentioning
confidence: 99%
“…70 The dopamine agonists, bromocriptine, and pramipexole, as well as L-dopa, have been reported to cause excessive daytime sleepiness. 71,72 Patients should be informed of the potential sedative side effects of dopaminergic medication and its implication on safe driving.…”
Section: Medication Related Effectsmentioning
confidence: 99%
“…It was not until 1999, however, after Frucht et al 70 reported that eight patients with PD had fallen asleep at the wheel, that concerns about sleep attacks arose. Seven of the eight patients were taking pramipexole, and it was suggested that this drug was the cause.…”
Section: Phase III Clinical Trial Results In Advanced Patientsmentioning
confidence: 99%
“…71,72 These reports engendered an unusual amount of interest, response, and controversy. 72,73 Based on the report by Frucht et al, 70 the FDA and health organizations around the world required amendments to package inserts, including a black box warning in the United States with a statement that patients should not drive until "they have gained sufficient experience with [pramipexole] to gauge whether or not it affects their mental and/or motor performance adversely. "…”
Section: Phase III Clinical Trial Results In Advanced Patientsmentioning
confidence: 99%
“…7 Nausea, dizziness and insomnia are similar between the two therapies. Sudden attacks of sleepiness resulting in motor vehicle accidents have been reported since approval, 25 leading to a warning on the label. Additional label changes since approval include warnings concerning pathological gambling and other impulse control disorders (ICD).…”
Section: Monotherapy With Ropinirole Immediate Releasementioning
confidence: 99%